Efficacy of saturated steam against Listeria innocua biofilm on common food-contact surfaces. (July 2021) - Hua, Zi; Younce, Frank; Tang, Juming; Ryu, Dojin; Rasco, Barbara; Hanrahan, Ines; Zhu, Mei-Jun
Abstract: Listeria monocytogenes forms biofilms on food-contact surfaces providing this pathogen with the potential to serve as a constant cross-contamination source. The objective of this study is to examine the efficacy of steam treatment against the biofilm of L. innocua, a well-known L. monocytogenes surrogate, on common food-contact surfaces using a pilot-scale steam treatment blancher. Saturated steam at 100 °C was effective in inactivating L. innocua in biofilms on all tested food-contact surfaces with a 6-sec steam treatment attaining a 2.4–3.1 log10 CFU/coupon (1.5 cm × 1.5 cm) reduction depending on the type of surface. However, the effectiveness of steam decreased dramatically during prolonged steam treatment with tailing effects more pronounced on rubber, low-density polyethylene (LDPE), polyvinyl chloride (PVC), followed by polyester (polyethylene terephthalate, PET), and then stainless steel (SS). A 30–180 s steam exposure at 100 °C caused a 4.0–6.4 log10 CFU/coupon reduction of L. innocua biofilm on SS, and 3.0–4.8, 2.8–4.2, 2.7–4.5 and 2.6–3.3 log10 reductions on PET, LDPE, PVC, and rubber surfaces, respectively. Organic soil from 1:10 diluted apple juice did not compromise the bactericidal effects of steam against L. innocua biofilm on all tested surfaces. Repeated steam exposure did not impact hydrophobicity and roughness parameters of SS, PET, and rubber coupons, but decreased hydrophobicity of PVC and LDPE, increased the Rz value of PVC, and decreased Rp and Rz values for LDPE surface. Data suggested that a short time steam exposure alone or in combination with other interventions likely provides effective mitigation treatments to control Listeria biofilm on SS, PET, and rubber surfaces. Highlights: Saturated steam caused a rapid kill of L. innocua biofilms on food contact surfaces. Effectiveness of steam decreased dramatically during prolonged steam treatment. Steam is most effective against L. innocua biofilms on stainless steel (SS) surface. Steam showed the least efficacy against L. innocua biofilms on rubber surface. Diluted apple juice did not impact efficacy of steam against L. innocua biofilm.